Design and construction of apnea and heart rate monitoring tools with abnormal condition notifications to prevent Sudden Infant Death Syndrome ( SIDS ) based on IOT ( Lost Data Analysis ) - erick dwi ananta (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2023)
ABSTRACT Sudden infant death syndrome or SIDS is the sudden death of a healthy infant under 1 year of age that occurs without any symptoms. This can be triggered by various factors, from the baby's sleeping position to the baby's physical condition that has not yet reached a certain stage of development. Checking the baby's body temperature and heart rate is a very important element to monitor the baby's condition and to prevent febrile seizures that cause epilepsy and decrease or increase the BPM value of the baby to ensure the baby is still beating his heart. Therefore, we need a device that can monitor the baby's body temperature and heart rate in real time and an efficient mechanism. In this study realtime monitoring with vital parameters, namely Respiration Rate using Piezo Electric sensors and heart rate monitoring using MAX30100 sensors, and ESP 32. The results of Heart Rate measurements have the largest difference value with comparison tools of 28,74% and smallest 0,00%. There is Loss of Respiration Rate Measurement data because Incorrect sensor placement. The output results can then be monitored through the website by doctors and other health workers and telegram notifications if conditions are not normal.